Factor Structure and Psychometric Properties of the Body Perception Questionnaire–Short Form (BPQ-SF) Among Chinese College Students - Wang, Nantong; Ren, Fen; Zhou, Xiaolu (Frontiers in Psychology, 2020)
Objective Body perception, including body awareness and reactivity, is featured in a range of mental health conditions. However, research on Chinese questionnaires assessing body perception has been surprisingly absent. The present study aimed to investigate the factor structure and psychometric properties of the Body Perception Questionnaire–Short Form (BPQ-SF) among Chinese. Methods the current sample included 688 Chinese college students. Self-report scales were used to measure body perception, somatization, and depressive somatic and psychological symptoms. Results Confirmatory factor analysis supported a three-factor model of the BPQ-SF, involving body awareness, supradiaphragmatic reactivity, and subdiaphragmatic reactivity. Good internal consistency and test–retest reliability were observed. Convergent validity was established by significant correlations with scores of somatization and somatic symptoms of depression. Divergent validity was evidenced by non-significant association with ratings on psychological symptoms of depression. The very short form of the body awareness subscale of BPQ can be an alternative to the body awareness subscale when scale length is the priority. Conclusion The BPQ-SF possessed three latent factors and demonstrated good psychometric properties that can measure body perception among Chinese in a reliable and valid way.